Hydrogel coating for hemodialysis catheter as well as preparation method and application of hydrogel coating

By applying polymer hydrogel coating on hemodialysis catheter, the complications caused by high catheter surface roughness are solved, and the lubrication, antibacterial and anticoagulation effects of the catheter are achieved, which significantly improves the dialysis quality and long-term patient Prognosis.

CN119405907APending Publication Date: 2025-02-11ZHU XIANYI MEMORIAL HOSPITAL OF TIANJIN MEDICAL UNIV (TIANJIN MEDICAL UNIV METABOLIC DISEASE HOSPITAL TIANJIN METABOLIC DISEASE PREVENTION CENT)
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411571757.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The surface roughness of existing hemodialysis catheters is high, resulting in complications such as central venous injury, catheter-related infections and thromboembolic complications, and there are challenges in maintaining structural integrity and drug activity in the body.

Method used

Using a hydrogel coating composed of polyvinyl alcohol, acrylamide, sulfobetaine methacrylate, potassium persulfate and polyethylene glycol diacrylate, the semi-interpenetrating network structure is formed through copolymerization and cross-linking, which improves the Lubricating, antibacterial and anticoagulant properties of the catheter.

Benefits of technology

It significantly reduces the friction coefficient on the catheter surface, improves antibacterial and antithrombotic properties, ensures the stability and hemocompatibility of the coating, and reduces the occurrence of catheter-related complications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a hydrogel coating for a hemodialysis catheter as well as a preparation method and application of the hydrogel coating. The functional hydrogel coating material is prepared from substances such as polyvinyl alcohol, acrylamide and sulfobetaine methacrylate in a thermal polymerization manner. The invention further discloses application of the hemodialysis catheter coating to improvement of lubrication, antibacterial and anticoagulation functions of a hemodialysis catheter, and the hemodialysis catheter coating has good stability and blood compatibility. Experimental results show that the hydrogel coating technology of the hemodialysis catheter can significantly improve the lubrication, bacterial adhesion resistance and thrombosis resistance functions of the hemodialysis catheter, and shows excellent bonding strength and blood compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hemodialysis catheters in biomedical engineering, and particularly relates to a functional hemodialysis catheter hydrogel coating and a preparation method and application thereof. Background Art

[0002] The number of patients with end-stage renal disease in my country who need hemodialysis treatment is increasing year by year. Most of these patients need to use central venous catheters for hemodialysis treatment temporarily or for a long time due to untimely diagnosis and treatment and poor vascular conditions. Central venous catheters can cause multiple complications such as central vein stenosis, thromboembolism, and catheter-related infection, which affect the patient's dialysis treatment effect and long-term prognosis.

[0003] During the process of catheter placement into the central vein, the lack of lubrication and high roughness of the catheter material surface can easily lead to venous intima damage, which in turn triggers inflammation and coagulation cascade reactions, which are considered to be the initial causes of various complications such as thrombosis and central vein stenosis. Our previous studies also revealed that catheter surface roughness may be one of the factors affecting central vein injury. In addition, studies have shown that the unevenness of the catheter surface can also promote bacterial attachment and colonization, thereby increasing the risk of catheter-related infection. Therefore, reducing the roughness of the catheter surface and improving its lubricity is one of the important measures to prevent catheter-related complications.

[0004] In recent years, hemodialysis catheters coated with drugs such as heparin and antimicrobial agents have appeared internationally, aiming to improve anticoagulation, antibacterial and other functions by locally releasing drugs. However, the application of these surface modification technologies may be limited by foreign body reactions in the body. At the same time, maintaining sufficient structural integrity and drug activity under continuous blood flow is also a key challenge facing coating materials. These problems limit the widespread clinical application of drug-coated hemodialysis catheters. Some studies have also applied functional polymer coatings, endothelial simulation and other technologies to improve the various functional properties of medical catheter surfaces. However, most of the current surface modification research on medical catheters is in the laboratory research stage, and there is still a lack of relevant research on hemodialysis catheters. Summary of the invention

[0005] The present invention overcomes the technical defects of existing hemodialysis catheters, such as high surface roughness and susceptibility to complications such as catheter-related infection and thromboembolism, and provides a hydrogel coating with sufficient lubrication, antibacterial and anticoagulant functions.

[0006] The purpose of the present invention is to reduce the risk of central vein injury caused by indwelling hemodialysis catheters and complications such as catheter-related infection and thromboembolism, optimize catheter function, improve dialysis quality, and improve the long-term prognosis of dialysis patients.

[0007] To achieve the above purpose, the present invention discloses the following technical contents: A hemodialysis catheter hydrogel coating, characterized in that it is composed of the following raw materials in parts by mass: Polyvinyl alcohol PVA 3-8 w / w% Acrylamide AM 7-27 w / w% Sulfobetaine methacrylate SBMA 7-27 w / w% Potassium Persulfate KPS 0.1-0.5 w / w% Polyethylene glycol diacrylate PEGDA 0.05-0.5 w / w%.

[0008] The present invention further discloses a method for preparing a hemodialysis catheter coating, which is characterized by being carried out in the following steps: Polyvinyl alcohol (PVA) was dissolved in deionized water at 85°C to prepare a PVA solution with a concentration of 3-8 w / w%, and cooled to room temperature; Dissolve acrylamide (AM) and sulfobetaine methacrylate (SBMA) in the above PVA solution at a mass ratio of 1:1, so that the concentrations of AM and SBMA both reach 7-27 w / w%, then add 0.1-0.5 w / w% potassium persulfate (KPS), and stir thoroughly to dissolve; Finally, 0.05-0.5 w / w% polyethylene glycol diacrylate (PEGDA) was added as a cross-linking agent and stirred evenly to obtain a pre-gel solution; the polyurethane catheter material was alternately washed with ethanol and deionized water, and after drying, it was immersed in the pre-gel solution, then taken out and polymerized at 80°C to prepare a semi-interpenetrating hydrogel coating.

[0009] The present invention further discloses the application of hemodialysis catheter coating in improving the lubrication, antibacterial and anticoagulant functions of hemodialysis catheter; the coating surface has good stability, which means that the coating surface is not easy to fall off, and the blood compatibility is still good. The experimental results show that the hemodialysis catheter hydrogel coating technology can significantly improve the lubrication, antibacterial adhesion and anti-thrombosis functions of the hemodialysis catheter, and has good bonding strength and blood compatibility.

[0010] The present invention mainly examines the common problems of high roughness and many complications of hemodialysis catheters currently used in clinical practice, with the focus on improving the surface roughness of the catheter and enhancing the lubrication function. The difficulty of the invention lies in improving the lubrication, antibacterial and anticoagulant functions of the catheter while ensuring the stability and blood compatibility of the coating on the catheter surface.

[0011] The innovation of the present invention lies in the hydrogel coating with lubricating, antibacterial and anticoagulant functions for hemodialysis catheters. The preparation technology of this coating material has not been reported in existing research.

[0012] The more detailed test method and experimental results of the present invention are as follows: 1. Regarding the selection of coating components: Sulfobetaine methacrylate is a zwitterionic compound with superhydrophilicity, which is beneficial to enhance the surface lubrication, anti-bacterial adhesion, anti-platelet adhesion and other properties of the hydrogel coating. Copolymerization of acrylamide and sulfobetaine methacrylate can improve the mechanical properties of the hydrogel network. The mass ratio of acrylamide to sulfobetaine methacrylate is set to 1:1. Under the appropriate crosslinker content, when the total content of the two monomers is less than 14 w / w%, the prepared hydrogel has a soft texture, insufficient mechanical strength, and poor anti-swelling ability; when the total content of the two monomers is higher than 54 w / w%, the prepared hydrogel has a hard texture and poor flexibility. Polyvinyl alcohol is a polyhydroxy long-chain polymer, which is beneficial to enhance the adhesion of the hydrogel coating to the catheter surface. At the same time, the long-chain polymer can be interspersed in the copolymer network to form a hydrogel with a semi-interpenetrating network structure, which is beneficial to improve the anti-swelling ability of the coating. When the content of polyvinyl alcohol is lower than 3 w / w%, the solution viscosity is too low, which is not conducive to the formation of the coating; when the content is higher than 8 w / w%, the solution viscosity is too high and it is easy to block the catheter lumen. Polyethylene glycol diacrylate is used as a crosslinker. If the content is too low, the mechanical strength of the hydrogel network will be insufficient. If the content is too high, the rigidity of the hydrogel will increase, increasing the risk of tissue irritation and coating fragmentation. Potassium persulfate is used as an initiator. If the content is too low, it will affect the reaction rate, and if the content is too high, it may cause side reactions. Therefore, when selecting and using these ingredients, we comprehensively consider various factors and set the above content range to achieve an appropriate performance balance.

[0013] 2. Observing the microscopic morphology of the hydrogel coating using an environmental scanning electron microscope, it can be seen that the microscopic surface of the hydrogel coating is very smooth, without the uneven surface seen on the surface of existing clinical hemodialysis catheters. The thickness of this hydrogel coating is only 7-8 microns, which will not affect the catheter lumen capacity (see Figure 1-3 ).

[0014] 3. Considering the force applied to the catheter in the blood vessel, we verified the shear force tolerance of the hydrogel coating (see Figure 4-5 ). The results showed that the coating could withstand a shear force of 11.99±1.20 kPa, which is much greater than the shear force of blood flow in the human central vein (normal range is 0.1-3 Pa). This indicates that the coating has good bonding strength.

[0015] 4. After the hydrophilicity test, the water contact angle of the polyurethane material surface after coating decreased from 91.00±4.92° in the uncoated state to 36.04±3.04° (see Figure 6-7 ), when the water contact angle is less than 50°, it can be classified as a superhydrophilic surface. Superhydrophilic surfaces have better biocompatibility, reduce the friction resistance between blood and the catheter surface, and improve anti-protein adhesion and anti-coagulation properties.

[0016] 5. We conducted a hemolysis test on polyurethane catheter materials with and without coating. According to ISO 10993-4 standard, if the hemolysis rate is <2%, the material is classified as non-hemolytic. The experimental results show that the hemolysis rate of catheter materials with and without coating is much less than 2%, and there is no significant difference (see Table 1). The results suggest that the coated polyurethane catheter surface also has good blood compatibility.

[0017]

[0018] 6. We used temporary and long-term hemodialysis catheters commonly used in clinical practice to measure the friction coefficients of the coated and uncoated catheters. The results showed that the friction coefficients of the coated catheters were significantly lower than those of the uncoated catheters, and the differences were statistically significant (see Figure 8-10 , Table 2). It was confirmed that the hydrogel coating effectively reduced the friction coefficient of the catheter and improved the lubrication performance.

[0019]

[0020] 7. We used Staphylococcus aureus and Escherichia coli, common bacterial species in catheter infection, to verify the anti-bacterial adhesion of the coating. The results showed that the number of both bacteria adhering to and growing on the surface of the uncoated catheter material was significantly higher (see Figure 11-12 ). Quantitative comparison of the counts of the two bacteria showed significant differences between the coated and non-coated groups (see Table 3), proving that the hydrogel coating improves the anti-bacterial adhesion ability of the catheter material surface.

[0021]

[0022] 8. We used platelet-rich plasma to conduct a platelet adhesion experiment on the catheter surface. The results showed that the number of platelets adhering to the surface of the uncoated catheter was significantly greater than that of the coated catheter, and most of the platelets showed dendritic deformation, indicating that the platelets were functionally activated, while the platelets on the surface of the coated catheter were still round particles with no activation (see Fig.13 ). Experiments have shown that hydrogel-coated catheters can effectively enhance the ability of the surface to resist platelet adhesion.

[0023] 9. We punctured the femoral artery and vein of rabbits to establish an extracorporeal circulation circuit, in which coated and non-coated catheters were connected in parallel. After one hour of circulation, the two catheters were removed. It can be seen that the residual thrombus content in the hydrogel-coated catheter was significantly less than that in the non-coated catheter, suggesting that the hydrogel coating improves the anticoagulant performance of the catheter (see Fig.14, Table 4).

[0024]

[0025] The positive effect of the hemodialysis catheter coating disclosed in the present invention compared with the prior art is that the hemodialysis catheter coating of the present invention improves the lubrication, antibacterial, anticoagulation and other functions, has sufficient bonding strength and blood compatibility, and can reduce the occurrence of catheter-related complications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an image of the surface of an uncoated hemodialysis catheter as seen by environmental scanning electron microscopy; Figure 2 This is an image of the surface of a hydrogel-coated hemodialysis catheter as seen by environmental scanning electron microscopy; Figure 3 is the cross-sectional thickness of the hydrogel coating observed by environmental scanning electron microscopy; Figure 4 The experimental photos for verifying the coating firmness; Figure 5 Schematic diagram of shear force experiment; Figure 6 It is the water contact angle of the surface of uncoated polyurethane material; Figure 7 is the water contact angle on the surface of the hydrogel-coated polyurethane material; Figure 8 The friction coefficient curves of coated and uncoated COVIDIEN MAHURKAR Acute Dual Lumen Catheter 13.5 Fr13.5 cm (temporary hemodialysis catheter); Fig. 9 The friction coefficient curves of coated and uncoated Medcomp 14.5Fr-24 cm PRE-CURVED Hemo-Flow DoubleLumen Catheter (long-term catheter); Fig.10 The friction coefficient comparison bar graph of two types of hemodialysis catheters with and without coating; Fig.11 The photos are of Staphylococcus aureus culture counts on the surfaces of uncoated and coated catheter materials; Fig.12 The photos are of the culture counts of Escherichia coli on the surfaces of uncoated and coated catheter materials; Fig.13 Environmental scanning electron microscopy images of platelet adhesion on the surfaces of uncoated and coated catheters; Fig.14 These are photos of the animal extracorporeal circulation experiment and the thrombus content in the uncoated and coated catheters after 1 hour of circulation. DETAILED DESCRIPTION

[0027] The present invention is described below by specific embodiments. Unless otherwise specified, the technical means used in the present invention are methods known to those skilled in the art. In addition, the embodiments should be understood as illustrative rather than limiting the scope of the present invention, and the essence and scope of the present invention are limited only by the claims. For those skilled in the art, various changes or modifications to the material composition and dosage in these embodiments, without departing from the essence and scope of the present invention, also belong to the protection scope of the present invention. The raw materials and reagents used in the present invention are all commercially available. Example

[0028] Preparation method of hydrogel coating: 0.8 g of polyvinyl alcohol (PVA) was dissolved in 10 mL of deionized water at 85 °C to obtain a PVA solution, which was then cooled to room temperature. 2.0 g of acrylamide (AM) and 2.0 g of sulfobetaine methacrylate (SBMA) were dissolved in the above PVA solution, and 40 mg of potassium persulfate (KPS) was added and stirred thoroughly to dissolve. Finally, 19 mg of polyethylene glycol diacrylate (PEGDA) was added as a crosslinker and stirred evenly to obtain a pre-gel solution. The polyurethane catheter material was alternately washed with ethanol and deionized water, dried, immersed in the pre-gel solution, and then taken out and polymerized at 80 °C. During the polymerization process, AM and SBMA copolymerized to form a network, and PVA was interspersed in the polymer network to form a semi-interpenetrating hydrogel coating.

[0029] After the preferred embodiments are described in detail, those familiar with the technology can clearly understand that various changes and modifications can be made without departing from the scope and spirit of the above patent application, and any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention are within the scope of the technical solution of the present invention. The present invention is not limited to the example implementation methods given in the specification.

Claims

1. A hemodialysis catheter hydrogel coating, characterized in that It is composed of the following raw materials in parts by weight: Polyvinyl alcohol PVA 3-8 w / w% Acrylamide AM 7-27 w / w% Sulfobetaine methacrylate SBMA 7-27 w / w% Potassium Persulfate KPS 0.1-0.5 w / w% Polyethylene glycol diacrylate PEGDA 0.05-0.5 w / w%.

2. The method for preparing the hemodialysis catheter coating according to claim 1, characterized in that Proceed as follows: Polyvinyl alcohol (PVA) was dissolved in deionized water at 85°C to prepare a PVA solution with a concentration of 3-8 w / w%, and cooled to room temperature; Dissolve acrylamide (AM) and sulfobetaine methacrylate SBMA in the above PVA solution at a mass ratio of 1:1, so that the concentrations of AM and SBMA both reach 7-27 w / w%, and then add 0.1-0.5 w / w% potassium persulfate KPS, and stir thoroughly to dissolve; Finally, 0.05-0.5 w / w% polyethylene glycol diacrylate PEGDA was added as a cross-linking agent and stirred evenly to obtain a pre-gel solution; the polyurethane catheter material was alternately washed with ethanol and deionized water, and after drying, it was immersed in the pre-gel solution, then taken out and polymerized at 80°C to prepare a semi-interpenetrating hydrogel coating.

3. Use of the hemodialysis catheter coating according to claim 1 for improving the surface stability of the coating; the improved surface stability of the coating means that the coating surface is not easy to fall off and the blood compatibility is still good.

4. Use of the coated hemodialysis catheter coating according to claim 1 for improving the lubrication, antibacterial and anticoagulant functions of the hemodialysis catheter.

Citation Information

Cited By

  • Long-term implantable gel composite woven medical catheter and forming method thereof

    CN119838121A

  • A long-term implantable gel composite braided medical catheter and its forming method

    CN119838121B